Integração entre televisão e redes sociais online: práticas comunicativas na cobertura do programa Roda Viva pelo Twitter - Erica Eloize Peroni Ferreira (2011)
This research examined the process of the television broadcasting on the online Twitter social network, accomplished by collaborators during the participatory transmission on Roda Viva TV program.The research objective was to investigate the practice of broadcasting from the proposed interaction between television and online social networks, based on the processes of media convergence . With the emergence of new media propelled by the advancement of Information and Communication Technology (ICT), we realize that there are similarities between old and new media from the processes of interactivity, aimed at making the traditional media more interactive. The focus of the study was kept on understanding the dynamics of communicative processes and the conversational interactions produced and seized through the intertwining of media (television and Internet), considering the role of the collaborator in the program as well as the relationships established with the audience. The methodology was guided by studies of the digital ethnography based on participant observation, combining the procedures of Content Analysis and Conversation Analysis to the handling and analysis. Content analysis was the method used to select the manifestations of users who use the tool, the tweets, to identify the hedging strategies used by staff from the categorization of modes of discursive construction of utterances. Subsequently, the conversational interactions identified by content analysis were submitted to conversational analysis in order to obtain concrete data on the nature of relationships and inferring the audience from the television content disseminated on the network. In the end, it was possible to verify that the standard of performance of employees is more prevalent in the research category inferential, ie, the tweets that refer to the employee's personal comments on the perception of the interview. The conversational analysis found the prevalence of short dialogues in conversation, presenting a greater number of these dialogues which refer to specific techniques of the program, the backstage and the in the performance of collaborators.